Type and Its Reproduction: On the Replication in Late Antique Sculpture Portrait - Obraztsova, Ksenia B. (Actual Problems of Theory and History of Art, 2023)
The article is dedicated to the phenomenon of replication in the Late Antique sculpture portrait. The various aspects of that phenomenon have been examined on the example of different categories of images such as emperors, philosophers, and private persons. All of them rely heavily on a type and use the principle of reproducing a given model to the great extent. That is the reason why, in a number of cases, it seems pointless to single out replica-related portraits from others. A higher degree of accuracy is more indicative of a workshop, than of a repetition that is conceptually detached from the one aimed to some degree at every monument. Other examples demonstrate that conscious repetition is hard to distinguish from accidental coincidences caused by a very limited number of types and interchangeable formal motifs.Special attention was given to the problem of replicas in the private portraiture. The existence of a few replicated images of the same person reveals a certain striving for recognizability. In a broader sense, it could have changed our understanding of the type-depending nature of the Late Antique portrait. The inscribed bases prove that the erection of multiple statues of one person was still a vivid practice in the period. However, the particular monuments labelled as replicas in the literature hardly stand out from the others in their typological and chronological groups. Moreover, as time went by, the repertoire of the physiognomic motifs and their possible combinations was inexorably reducing. Thus, there was no need for an accurate replication to create two recognizable representations of the same person: the correct type and the very basic features coped finely with the task on their own.
Keywords: sculpture portrait; Late Antique art; replica; emperor portrait; philosopher portrait; private person portrait; principle of reproducing